2020
DOI: 10.2147/opth.s278589
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Analysis of Swept-Source Optical Coherence Tomography and Partial Coherence Interferometry Biometers in the Prediction of Cataract Surgery Refractive Outcomes</p>

Abstract: Purpose: To compare the accuracy of pre-operative corneal measurements obtained with four devices, and the refractive outcomes of two optical biometers. Setting: Private practice. Design: Retrospective. Methods: Data taken from biometric measurements on 299 consecutive eyes prior to cataract surgery were retrospectively analyzed using the Argos SS-Optical Biometer and the Lenstar LS900 PCI optical biometer. As part of the standard cataract surgery preoperative exam, patients also underwent placido disk topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…10 However, some caution is suggested, as CMAL revealed a proportional bias leading to lower AL values in longer eyes: this means that, in eyes longer than 30.0 mm, CMAL is likely to provide AL values shorter than Argos with subsequent IOL power overestimation. This difference may depend on the fact that CMAL was developed from AL measurements obtained by optical low-coherence reflectometry, which can provide different measurements of LT when compared with swept-source OCT. 5 Overall, the 2 optical biometers calculated similar IOL powers using the SRK/T formula, as only 9% of eyes revealed a difference in IOL power >0.50 D. The percentage would probably have been higher if more eyes with AL >30 mm had been enrolled, as the difference between the Argos and the IOLMaster is proportional to AL, as previously noted. Future studies are required to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…10 However, some caution is suggested, as CMAL revealed a proportional bias leading to lower AL values in longer eyes: this means that, in eyes longer than 30.0 mm, CMAL is likely to provide AL values shorter than Argos with subsequent IOL power overestimation. This difference may depend on the fact that CMAL was developed from AL measurements obtained by optical low-coherence reflectometry, which can provide different measurements of LT when compared with swept-source OCT. 5 Overall, the 2 optical biometers calculated similar IOL powers using the SRK/T formula, as only 9% of eyes revealed a difference in IOL power >0.50 D. The percentage would probably have been higher if more eyes with AL >30 mm had been enrolled, as the difference between the Argos and the IOLMaster is proportional to AL, as previously noted. Future studies are required to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 62%
“…3,4 Several authors subsequently demonstrated that the Argos displays a tendency to measure long eyes shorter in comparison to optical biometers using the group refractive index, such as the IOLMaster 700 (Carl Zeiss Meditec), the LENSTAR LS900 (Haag-Streit AG), the OA-2000 (Tomey), and the Pentacam AXL (Oculus). [5][6][7] The aim of this study was to confirm that AL measurements by the Argos in myopic eyes are shorter than those provided by an optical biometer relying on the group refractive index (IOLMaster 700) and to assess whether they are similar to those obtained by using the most important corrections recently developed to shorten the AL measured in long eyes by biometers based on the group refractive index: the original Wang-Koch AL adjustment, Holladay polynomial equations, and Cooke-modified AL (CMAL). [8][9][10]…”
mentioning
confidence: 99%
“…Several studies have been excluded as they have compared results of optical biometry in healthy but not in cataract patients [ 17 22 ], did not compare outcomes of PCI/LCOR with SS-OCT devices [ 23 29 ] or both [ 30 ]. Finally, fourteen studies were included in the final analysis (Table 1 ), which presented results of 2,459 eyes of at least 1,853 patients (since in one study [ 31 ] only the number of eyes, and not patients was reported).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias assessment [Supplementary Table 1 ] represents that several of the studies did not explain in detail the reason for technical failure [ 13 , 24 , 31 , 34 , 36 , 38 40 ]. There are some usability differences between the devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation